Tortuous Carotid Artery Extended to Neck Level IIb Mimicking the Metastatic Mass - Uzun, Lokman (Case Rep Otolaryngol, 2016)
Specifically in neck level IIb, the expected normal anatomy does not contain any vital structures and consequently it might direct a surgeon to perform rapid surgical dissection of tissues. Therefore aberrant anatomy of the vessels in the patients may be overlooked during neck dissection. Unexpected and potentially devastating injuries can be avoided by respecting the possible aberrant anatomy in any level of the neck. In this case report, a 74-year-old man was presented with laryngeal carcinoma who was treated with laryngectomy and bilateral neck dissection. During the left side neck dissection, tortuous internal carotid artery imitating a metastatic mass was unexpectedly encountered in level IIb. As in this case, surgeons should keep in mind possible aberrant anatomy during the neck dissection and perform surgery staying in surgical principles to be safe for an unforeseen and potential dangerous injuries.